Clinical evidences of urea at high concentration on skin and annexes. (29th November 2020) - Starace, Michela; Alessandrini, Aurora; Piraccini, Bianca Maria
Abstract: The antiproliferative, keratolytic, moisturizing and emollient properties of urea are already known. Clinical evidences of urea at high concentration indicate its important role in the presence of hyperkeratosis that, if severe or localized in specific body areas, may cause discomfort to the patient and may interfere with absorption of topical drugs, delaying response to treatment. Other important uses of urea at high concentration are on the scalp and on nail plate. The keratolytic effect of urea is well‐tolerated and virtually free from side effects. Compliance with topical therapy is directly related to the aesthetic and sensory acceptability of a topical agent that may considerably vary in odour, spreadability and post‐application residue.